Differential expression of exosomal microRNAs in fresh and senescent apheresis platelet concentrates. (17th November 2022) - Mi, Ziyue; Gong, Li; Kong, Yujie; Zhao, Peizhe; Yin, Yonghua; Xu, Haixia; Tian, Li; Liu, Zhong
Abstract: Patients have a high risk of suffering adverse reactions after receiving platelet products stored for 5 days. Bioactive exosomes in platelet products can be accumulated during storage, which is associated with adverse reactions. MicroRNAs are one of the critical cargoes in exosomes, which participate in cell differentiation, metabolism, and immunomodulation. This study intends to elucidate and analyze the differential expression of exosomal microRNAs in apheresis platelet concentrates during storage and predict the potential functions of target genes. Apheresis platelet concentrates were used to isolate exosomes by ultracentrifugation. Exosomes were phenotyped by western blot, transmission electron microscopy, and nano flow cytometry. The differential expression of the exosomal microRNAs was obtained by a microarray test using four bags of apheresis platelets stored for 5 days compared with 1 day. The differentially expressed microRNAs between the two time points were identified, and their target genes were analyzed by miRWalk and miRDB. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to predict the target genes' functions. Fifteen bags of apheresis platelet concentrates stored for 1 day and 5 days were used to verify the microarray results by quantitative reverse transcription-polymerase chain reactions (qRT-PCR). There were 134 microRNAs in total expressed differently in the two groups (day 1 and day 5), with 57 microRNAs up-regulated and 77 down-regulated (|fold change| > 2.0 and P  < .05). Thirteen up-regulated microRNAs (hsa-miR-22-3p, hsa-miR-223-3p, hsa-miR-21-5p, hsa-miR-23a-3p, hsa-miR-320b, hsa-let-7a-5p, hsa-miR-25-3p, hsa-miR-126-3p, hsa-miR-320c, hsa-miR-342-3p, hsa-miR-320d, hsa-miR-328-3p, and hsa-miR-320e) detected in all samples were selected to validate the results. The qRT-PCR results showed that five (hsa-miR-22-3p, hsa-miR-223-3p, hsa-miR-21-5p, hsa-miR-23a-3p, and hsa-miR-320b) of them were increased more than 10-fold ( P  < .001); four (hsa-let-7a-5p, hsa-miR-25-3p, hsa-miR-126-3p, hsa-miR-320c) more than five-fold ( P  < .001); two (hsa-miR-342-3p and hsa-miR-320d) more than two-fold ( P  < .05); and two (hsa-miR-328-3p and hsa-miR-320e) more than two-fold ( P  > .05). Specifically, hsa-miR-22-3p increased 14.6-fold; hsa-miR-223-3p increased 13.0-fold; and hsa-miR-21-5p increased 12.0-fold. Based on bioinformatics functional analysis, target genes of top nine microRNAs (hsa-miR-22-3p, hsa-miR-223-3p, hsa-miR-21-5p, hsa-miR-23a-3p, hsa-miR-320b, hsa-let-7a-5p, hsa-miR-25-3p, hsa-miR-126-3p, and hsa-miR-320c) were annotated with positive regulation of cell proliferation and nervous system development, and mainly enriched in regulating pluripotency of stem cells signaling pathway, prolactin signaling pathway, and FoxO signaling pathway, etc. The prolactin, FoxO, ErbB, and TNF signaling pathway were relevant to immunomodulation. In particular, hsa-miR-22-3p expression was the most different during storage, with a fold change of 14.6, which might be a key mediator. Plain Language Summary: What is the context? Platelet transfusion is a widely used clinical treatment, but it is not totally safe. Side effects may happen to patients who receive the "older" platelet products. Exosomes in platelet products can be transfused to patients while receiving blood. Exosomes are accumulated in platelet products during storage. MicroRNAs are one of the important cargoes in exosomes, which can be delivered to the target cells, thus affecting their functions. This study aims to investigate and analyze the differential expression profiling of exosomal microRNAs in apheresis platelet concentrates during storage, and predict the potential function of the target genes. We found out the top nine differentially expressed microRNAs got involved in positive regulation of cell proliferation and nervous system development, and mainly enriched in regulating pluripotency of stem cells signaling pathway, prolactin signaling pathway, and FoxO signaling pathway, etc. What's new? Our study is the first one to test the exosomal microRNAs in the apheresis platelet concentrates. The apheresis platelet concentrates were stored for 1 day and 5 days. Compared the two time points, we obtained the differential expression profiling of exosomal microRNAs. Based on bioinformatics analyses and qRT-PCR results, we provided nine up-regulated microRNAs which might be critical mediators to communicate with target cells after transfusing. What's the impact? This study expands our knowledge of exosomal microRNA expression profiling from apheresis platelet concentrates along different storage periods. This might be relevant to immunomodulation in post transfusion situations.